2nd International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings (University of Maribor Press, 2020)
The 2nd International Conference on Technologies & Business Models for Circular Economy (TBMCE) was devoted to presentations of circular economy concepts, technologies and methodologies that contribute to the shift of business entities and society as a whole to a more responsible, circular management of resources. In the framework of TBMCE 2019, we presented the Strategic Research and Innovative Partnership –Network for the Transition to Circular Economy (SRIP-CE) as a platform for establishing a successful long-term public-private partnership. The conference program included panel discussions, plenary and keynote sessions, oral and poster presentations on the following topics: Sustainable energy, Biomass and alternative raw materials, Circular business models, Secondary raw materials and functional materials, ICT in Circular Economy, Processes and technologies. TBMCE 2019 was organized by Faculty of Chemistry and Chemical Engineering, University of Maribor and held in Portorož, Slovenia at the Grand Hotel Bernardin from October 24th to October 25th, 2019. The event was under the patronage of Ministry of Economic Development and Technology.